Practical privacy measures in blockchains - Omar S, Saleh; Osman, Ghazali; Idris, Norbik Bashah (Springer Cham, 2020)
The Blockchain Technology has recently been a hot topic proposed in many industries such as Financial, Healthcare, Business, E-Government, Education, etc. The Blockchain can simply be defined as a distributed database or public ledger that contains records of all digital transactions/events that have transpired amongst the parties involved. The technology itself is comprised of other more fundamental knowledge namely: cryptography, distributed system, network and game theory. Thus at the more basic level, the blockchain components include functions such as hash, asymmetric cryptography, digital signatures, peer-to-peer network protocols and some elements of a “proof of correctness/work” resulting from a game-like setup. Against a backdrop of such a mixture of functions, “privacy” has emerged to be one of the new challenges in any Blockchain implementation. This research aims to investigate the techniques that can be used to successfully manage privacy in the blockchains. The work has identified the requirements and analyzed the techniques that can be used. Finally, the work was also extended to an analysis on the performance evaluation of blockchains in managing privacy albeit focusing on a specific blockchain—the Hyperledger fabric platform.